Peri-operative management of pheochromocytoma with intravenous urapidil to prevent hemodynamic instability: A 17-year experience - Patrick Tauzin-Fin; Kévin Barrucand; Musa Sesay; Stéphanie Roullet; Philippe Gosse; Jean-Christophe Bernhard; Gregoire Robert; François Sztark (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Surgery for pheochromocytoma (PCC) can cause excessive catecholamine release with severe hypertension. Alpha blockade is the mainstay of preoperative management. The aim of this study was to evaluate the efficacy and tolerance of intra-venous (IV) urapidil, a competitive short acting α1 receptor antagonist, in the prevention of peri-operative hemodynamic instability of patients with PCC. Material and Methods: This retrospective observational study included 75 patients (79 PCC) for PCC removal surgery from 2001 to 2017 at the Bordeaux University Hospital. They received, 3 days before surgery, continuous intravenous infusion of urapidil with stepwise increase to the maximum tolerated dose. Urapidil was maintained during the procedure and stopped after clamping the adrenal vein. Plasma catecholamine concentrations were measured during surgery. Hypertensive peaks (SAP >160 mmHg) and tachycardia >100 beats/min were treated with boluses of nicardipine 2 mg and esmolol 0.5 mg/kg. Results: We recorded 20/79 (25%) cases with systolic arterial pressure (SAP) >180 mmHg. Only 11/79 (14%) had hypotension with SAP <80 mmHg. Peaks of catecholamine secretions were observed preferentially during peritoneal insufflation and tumor dissection (P < 0.05). A correlation was found between tumor size (mm) and the highest norepinephrine levels [r = 0.288, P = 0.015], and between hypertensive peaks (mmHg) and the highest norepinephrine levels [r = 0.45, P = 0.017]. No mortality was reported. The median [range] postoperative hospital stay was 4 [2-9] days. Conclusion: IV urapidil limits hypertensive and hypotensive peaks during PCC surgery, and corresponds to surgical imperatives allowing a short hospital stay, due to its "on-off" effect.